THE CHAMPION OF THE GRASSROOTS REVISITED: An Episode of Emha Ainun Najib's Stage Performance and Environmental Activism against Cement-Mining Corporations in Northern Kendeng of Pati, Indonesia - Faizi, Fuad; Lukito, Ratno; Fauzan, Achmad Uzair (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2022)
Emha Ainun Najib (Cak Nun) is a charismatic and controversial Muslim cultural leader who has a wide audience in Indonesia. Along with an ensemble band called Kiai Kanjeng, he has monthly performances in various parts of Indonesia Adding to that, they are occasionally invited by institutions, individuals, or businesses. In the New Order era, on behalf of the disadvantaged, Cak Nun’s criticisms against a highly controversial dam project in 1980–1991 showed his rebellious tendencies in the face of state and elite despotism. As a result, Rasmussen (2010) eventually refers to him as “the champion of the grassroots.” However, since his involvement in the corporation-induced mudflow of Lapindo in Sidoarjo in 2006, his stand on the grassroots has actually been doubted. However, based on his recent stage performances in several regions hit by industrially-induced environmental crises, particularly in Pati's northern Kendeng, some groups have begun to question whether the assumption that Cak Nun is “the champion of the grassroots” is still relevant. By elaborating on the ways in which various onstage and backstage stories were formed in northern Kendeng, this paper argues that Cak Nun is perceived to deliver confusing messages, resulting in the affected communities becoming more divided and fragmented.